TRAF6 Suppresses the Development of Pulmonary Fibrosis by Attenuating the Activation of Fibroblasts - Min, Jiali; Li, Qiao; Liu, Suosi; Wang, Qianrong; Yin, Min; Zhang, Yan; Yan, Jun; Cui, Bing; Liu, Shanshan (Frontiers in Pharmacology, 2022)
Pulmonary fibrosis (PF) has a high mortality rate, and its pathogenesis is unknown. TNF receptor-associated factor 6 (TRAF6), a signal transducer for inflammatory signaling, plays crucial roles in the pathogenesis of immune diseases. However, its function in PF remains unknown. Herein, we demonstrated that lungs from mice with bleomycin (BLM)-induced PF were characterized by decreased expression of TRAF6 in lung fibroblasts. Enhancing TRAF6 expression protected mice from BLM-induced PF coupled with a significant reduction in fibroblast differentiation. Furthermore, we demonstrated that overexpression of TRAF6 reversed the activation of myofibroblasts from PF mice by reducing the expression of Wnt3a and subsequently suppressing Wnt/β-catenin signaling. Additionally, the abundance of Tribbles pseudokinase 3 (TRIB3), a stress sensor, was negatively correlated with the abundance of TRAF6 in lung fibroblasts. TRIB3 overexpression decreased TRAF6 abundance by reducing TRAF6 stability in lung fibroblasts during PF. Mechanistic studies revealed that TRIB3 bound to TRAF6 and accelerated basal TRAF6 ubiquitination and degradation. Collectively, our data indicate that reduced TRAF6 expression in fibroblasts is essential for the progression of PF, and therefore, genetically increasing TRAF6 expression or disrupting the TRIB3-TRAF6 interaction could be potential therapeutic strategies for ﬁbroproliferative lung diseases in clinical settings.